Pengaruh Kondisi Post Mortem Ikan Patin (Pangasius Djambal) dengan Kematian Menggelepar yang Disimpan pada Suhu Berbeda Terhadap Mutu Filletnya - Susi Lestari; Ace Baehaki; Imam Mahdi Rahmatullah (Universitas Sriwijaya, 2020)
This study aimed to determine the quality of differences in catfish fillets made in the pre rigor, rigor mortis, and post rigorstage. This research is divided into 2 stages, the preliminary research stage and further research. Data processing is carried out quantitatively by analyzing parametric statistical data with Anova and non parametric tests with the Kruskal Wallis test. The parameters of this study include stiffness index, pH value, TVB and organoleptic test. Preliminary research results on catfish at the meeting room temperature pre rigor, rigor mortis, and post rigor are interrelated at 0, 1.5, 9 hours with rigor index values of 0%, 27%, 5% and time of pre rigor and rigor mortis at cold temperatures at 0 and 6 hours with rigor index values of 0% and 70%.. In the main study it was shown that all TVB comparisons are significantly different and at pH values all are significantly different except for cold temperature pre rigor and post rigor comparisons. The results of organoleptic fillets showed significantly different results in the comparison of rigor mortis and post rigor phases in the part of testing the appearance of meat integrity and color appearance of filllet meat at cold temperatures.